Antioxidant activity, ascorbic acid and total phenol of exotic fruits occurring in Brazil - de Assis, Sandra Aparecida [UNESP]; Rebuglio Vellosa, Jose Carlos [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Khalil, Najeh Maissar [UNESP]; da Silva Cerqueira Leite, Katia Maria [UNESP]; Geraldo Martins, Antonio Baldo [UNESP]; Mascarenhas de Faria Oliveira, Olga Maria [UNESP] (Taylor & Francis Ltd, 2009)
The antioxidant activity, ascorbic acid and phenolic content were studied in 10 exotic fruits from Brazil: abiu, acerola, wax jambu, cashew, mamey sapote, carambola or star fruit, Surinam cherry, longan, sapodilla and jaboticaba. The ascorbic acid was determined by 2,6-dichloroindophenol titrimetic methods and total phenols were measured colorimetrically using the Folin-Ciocalteu reagent. The antioxidant activity was investigated with three different methods: hypochlorous acid scavenging activity, 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation decolorization assay, and 2,2-diphenyl-1-picrylhydrazyl radical scavenging method. The highest content of vitamin C (1,525.00 mg/100 g pulp) occurred in acerola. The total phenol content was higher in abiu, acerola, Surinam cherry and sapodilla. In relation to antioxidant activity, acerola has showed the great values in all three different methods tested. It was found that the fruits have a significant antioxidant effect when tested by each method, respectively, and these antioxidant capacities are promising. The sample concentration also influenced its antioxidant power.
Keywords: Fruits; antioxidants; reactive oxygen species; phenol content; ascorbic acid